A case of atopic dermatitis with hypohidrosis improved after dupilumab treatment. Issue 6 (20th September 2020) - Imamura, Shinya; Washio, Ken; Mizuno, Mayuko; Oda, Yoshiko; Ogura, Kanako; Fukunaga, Atsushi; Nishigori, Chikako
Abstract : This is a case of AD complicated with hypohidrosis, and the symptoms of the AD as well as perspiration were dramatically improved after dupilumab treatment.